2006
DOI: 10.1136/bjo.2006.097352
|View full text |Cite
|
Sign up to set email alerts
|

Expression of haematopoietic stem cell markers, CD133 and CD34 on human corneal keratocytes

Abstract: Human keratocytes express the haematopoietic stem cell markers CD133 and CD34. This expression decreases with time in culture, with most but not all cells losing expression. On the basis of these markers, the corneal stroma shows a heterogeneous population of cells. Expression or down regulation of expression of these molecules could represent different stages of activation of these cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 20 publications
(19 reference statements)
1
30
0
Order By: Relevance
“…However, the current minimal criteria for MSC are not ideal for assessing the phenotype of CSSC, as one criterion states that MSC should not express CD34. Nevertheless, our group has showed CD34 is a well-established marker for quiescent keratocytes in vivo [14,15], and CD34 has been linked ABCG2 is a molecular determinant of the side population phenotype that is characteristic of stem cells, and has been used previously to identify CSSC [26,44]. ABCG2 is expressed by a wide variety of stem cells including haematopoietic stem cells [45], embryonic stem cells [46], neural stem cells [47], and perhaps most relevantly limbal epithelial stem cells [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the current minimal criteria for MSC are not ideal for assessing the phenotype of CSSC, as one criterion states that MSC should not express CD34. Nevertheless, our group has showed CD34 is a well-established marker for quiescent keratocytes in vivo [14,15], and CD34 has been linked ABCG2 is a molecular determinant of the side population phenotype that is characteristic of stem cells, and has been used previously to identify CSSC [26,44]. ABCG2 is expressed by a wide variety of stem cells including haematopoietic stem cells [45], embryonic stem cells [46], neural stem cells [47], and perhaps most relevantly limbal epithelial stem cells [48].…”
Section: Discussionmentioning
confidence: 99%
“…Markers traditionally used to identify the keratocyte phenotype include aldehyde dehydrogenase (ALDH), keratocan, CD133 and, as originally identified by our group, CD34 [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominin-1 or CD133, a stem cell marker, was detected n the adult and P10 cornea gene expression patterns and presence of the protein was further confirmed in corneal protein extracts. Two recent studies identified this marker in the corneal stroma and a subset of corneal keratocytes (Perrella et al 2007;Thill et al 2007). While prominin-1 is known as a hematopoietic stem cell marker, its expression at such high level in the cornea suggests that it may be a marker for the subset of keratocytes that are derived from bone marrow progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Having enriched NCSCs, these free‐floating spheroids attained CSK phenotype after further treatment with bFGF, TGFβ3 and L A 2 P, a reported CSK differentiation protocol 46. The spheroid cells positively expressed CD34, ALDH3A1 and Col8A2, markers for CSKs,47, 48 and they also had low expression levels of KERA and its synthesizing enzymes (B3GNT7, CHST6). In particular, CD34 immunoreactivity was detected in almost half of cell population inside the treated spheroids.…”
Section: Discussionmentioning
confidence: 99%